ANALYSIS OF VALUE ADDED AND MARKETING OF PROCESSED CASSAVA PRODUCTS IN SUCI RIVER FARMER GROUP IN PASAR PEDATI VILLAGE BENGKULU CENTRAL - Nadia Minfaz Afanin; Irnad; Sriyoto Sriyoto (Journal of Agri Socio Economics and Business, 2023)
This study aims to see how much added value and analysis of the marketing system for processed cassava products, analyze marketing (product distribution, marketing channels, producer's share) for processed cassava products by the Sungai Suci farmer group in Pasar Pedati Village, Central Bengkulu Regency and how the marketing system for processed cassava in the Sungai Suci farmer group in Pasar Village Central Bengkulu Carrier. The method of data analysis in this research is quantitative and descriptive analysis.          The results of the value added obtained from the processing of cassava opak is IDR 3,953/Kg with an added value ratio of 53%. The added value obtained from processing rengginang sweet potato in one kilogram is IDR 4,703/Kg with a ratio of 59%. The added value obtained from processing mocaf flour in one kilogram is IDR 2,441/Kg with a ratio of 49%.    To find out the marketing system for the three processed cassava products, namely (opaque, rengginang, mocaf flour) calculations were carried out using marketing channel analysis, margins, and producer's share. There are two marketing channels, namely: producers (farmer groups) – end consumers (opaque, rengginang, mocaf flour), farmer group producers) – retailers) – consumers (opaque and rengginang). The value of the marketing margin and profit margin obtained is the same as that of channel I (opaque and rengginang) which are IDR 5,000/Kg and IDR 4,013/Kg. the value of the producer's share of marketing I processed opaque and rengginang is Rp 83.33% and 80.00%.